Sexual Assault through a Forensic Lens: Understanding Drug Facilitated Sexual Assault Issues in Nepal - Gautam, Lata; Grela, Agatha; Satyal, Jaya (Annapurna Journal of Health Sciences, 2023)
Sexual assaults and drug facilitated sexual assaults (DFSA) are becoming a serious problem in Nepal. The increasing number of DFSA cases being reported in the country highlight the urgent need to focus our efforts on several areas, including: (i) capacity building on crime scene examination and forensic analysis of sexual assault cases, (ii) moral and sexual education, and public awareness programmes in schools, and (iii) revised policy and practice in handling of sexual assault cases. Therefore, our work is focused on understanding changing public perception and attitude in society as well as shifting behaviour among law enforcement agencies such as police and judiciary. In relation to these issues, we have been working collaboratively for the past few years with different organisations and stakeholder groups. Some examples include: (i) running various events to increase awareness (e.g. TV programmes, newspaper articles and interviews, extra-curricular activities in schools); (ii) organising capacity building training to forensic scientists; and (iii) organising workshops to bring together a variety of stakeholders. Here, in this paper, we present our key insights, experience and lessons learnt from these activities. We highlight the need to expand the collaboration effectively among the key stakeholders due to the complex nature of DFSA cases. We also recommend increasing visibility and expansion of One Stop Crisis Management Centres throughout the country with focus on hard-to-reach areas.